Frequência e significado clínico da expressão da glicoproteína P e da proteína relacionada a resistência a múltiplas drogas na leucemia mielóide aguda - Cunha, Andréa Luciana Araújo da (2013)
Despite the advances in the cure rate for acute myeloid leukemia, a considerable number of patients die from their disease due to the occurrence of multidrug resistance (MDR). Overexpression of the transporter proteins P-glycoprotein (Pgp) and multidrug resistance-associated protein (MRP) confer resistance to the treatment these leukemias. OBJECTIVE: To analyze the expression of the Gpp and MRP1 in patients with AML by flow cytometry (FC) and to determine the correlation between expression and demographic and also clinical and laboratorial variables. METHODS: Bone marrow and peripheral blood samples from 346 patients with a diagnosis of AML were assessed for the expression of Pgp and MRP1 by FC. RESULTS: The expression of Pgp and MRP1 was found in 111 (32.1%) and 133 (38.4%) patients, respectively, with greater prevalence in older patients and lower in adolescents, observing also a high incidence in patients with refractory disease, recurrence and secondary in comparison with the cases of de novo AML. Regarding the laboratory findings, we observed a higher correlation statistically significant between the expression of Pgp and MRP1 in AML CD34+ and FAB AML M7, M5A and M2 and lower the M3 subtype, not observed statistically significant correlation between the phenotype MDR and other laboratory data such with hemoglobin, leukocyte count, platelet count, aberrant expression of lymphoid antigens (CD2, CD7 and CD19) and clinical signs related to the disease. CONCLUSIONS: The results showed that the detection of MDR phenotype by flow cytometry can be a molecular marker for prognosis independent patients diagnosed with AML.